Text Linguistics and Translation. With Special Consideration of the Performance of Machine Translation Systems in the Field of Text Organisation - Albrecht, Jorn (Acta Universitatis Danubius. Communicatio, 2022)
Eugenio Coseriu’s introductory lecture on text linguistics, edited and revised by the author of these lines, presents two forms of text linguistics: text linguistics in the narrower sense, i.e. “transphrastic grammar” tied to a specific language, and text linguistics in the broader sense, the “linguistics of meaning”. This latter form of text linguistics examines how the signs of the text of any language give meaning to the text as a whole not only through what they denote but also through what they evoke. This article attempts to bring Coseriu’s remarks on text linguistics into a systematic context with the problem of translation. In doing so, it also examines – for the time being only in a rudimentary way – what corpus-based machine translation systems can achieve in this area and where they reach their limits.